Exploring Scientific Indications of "Arham" through Medical Technology in Ar-Ra'd Verse 8 - Fadhilah, Umi; Azizah, Alfiyatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Surah Ar-Ra'd, the 13th chapter of the Quran, offers profound guidance and wisdom for humanity, encompassing various aspects of life. Within this surah, verse 8 introduces the term "Arham," derived from the root word رحم (raḥima), signifying mercy and compassion. "Arham" is intricately linked to Allah's attributes of mercy and encompasses all aspects of creation, including kinship relations and the womb. This article delves into the scientific indications embedded in Surah Ar-Ra'd, verse 8, particularly focusing on the interpretation of "Arham" as the womb and its correlation with modern medical instrumentation technology. Drawing from thematic interpretation methodologies, this article examines the theme of the Quran, identifies relevant verses, and prioritizes discussions based on Quranic language style. The thematic analysis of "Arham" unfolds through the lens of medical instrumentation technology, elucidating the advancements in understanding the womb's structure, health, and predictive capabilities. By integrating qualitative literature-based methods, the discussion not only presents factual information but also explores the underlying meanings and implications of "Arham." This thematic interpretation aims to enhance understanding and appreciation of the Quran's guidance while highlighting the compatibility between religious teachings and scientific advancements. The discussion underscores the significance of embracing both spiritual and scientific knowledge in enriching human comprehension and addressing societal issues.